2023
DOI: 10.1002/adbi.202300083
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Protein Degradation: Principles, Strategies, and Applications

Abstract: Protein degradation is a general process to maintain cell homeostasis. The intracellular protein quality control system mainly includes the ubiquitin‐proteasome system and the lysosome pathway. Inspired by the physiological process, strategies to degrade specific proteins have developed, which emerge as potent and effective tools in biological research and drug discovery. This review focuses on recent advances in targeted protein degradation techniques, summarizing the principles, advantages, and challenges. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 151 publications
0
1
0
Order By: Relevance
“…The target protein degradation strategies such as PROTAC and AUTAC have become a new trend in drug development. 27 Different from the traditional small-molecular inhibitors, PROTACs can potentially play a catalytic role by facilitating multiple rounds of degradation of the target protein, thus efficiently improving the inhibitory potency. 28 It has been reported that PROTACs were developed to target multiple targets to degrade the targets simultaneously.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The target protein degradation strategies such as PROTAC and AUTAC have become a new trend in drug development. 27 Different from the traditional small-molecular inhibitors, PROTACs can potentially play a catalytic role by facilitating multiple rounds of degradation of the target protein, thus efficiently improving the inhibitory potency. 28 It has been reported that PROTACs were developed to target multiple targets to degrade the targets simultaneously.…”
Section: ■ Discussionmentioning
confidence: 99%